Safety study of live, oral human rotavirus vaccine: A cohort study in United States health insurance plans. Issue 7 (3rd July 2018) - Hoffman, Veena; Abu-Elyazeed, Remon; Enger, Cheryl; Esposito, Daina B.; Doherty, Michael C.; Quinlan, Scott C.; Skerry, Kathleen; Holick, Crystal N.; Basile, Peter; Friedland, Leonard R.; Praet, Nicolas; Wéry, Stéphanie; et al.
ABSTRACT: As part of a regulatory commitment for post-licensure safety monitoring of live, oral human rotavirus vaccine (RV1), this study compared the incidence rates (IR) of intussusception, acute lower respiratory tract infection (LRTI) hospitalization, Kawasaki disease, convulsion, and mortality in RV1 recipients versus inactivated poliovirus vaccine (IPV) recipients in concurrent (cIPV) and recent historical (hIPV) comparison cohorts. Vaccine recipients were identified in 2 claims databases from August 2008 – June 2013 (RV1 and cIPV) and January 2004 – July 2008 (hIPV). Outcomes were identified in the 0–59 days following the first 2 vaccine doses. Intussusception, Kawasaki disease, and convulsion were confirmed via medical record review. Outcome IRs were estimated. Incidence rate ratios (IRRs) were obtained from Poisson regression models. A post-hoc self-controlled case series (SCCS) analysis compared convulsion IRs in a 0–7 day post-vaccination period to a 15–30 day post-vaccination period. We identified 57, 931 RV1, 173, 384 cIPV, and 159, 344 hIPV recipients. No increased risks for intussusception, LRTI, Kawasaki disease, or mortality were observed. The convulsion IRRs were elevated following RV1 Dose 1 (cIPV: 2.07, 95% confidence interval [CI]: 1.27 – 3.38; hIPV: 2.05, 95% CI: 1.24 – 3.38), a finding which is inconclusive as it was observed in only one of the claims databases. The IRR following RV1 Dose 1 in the SCCS analysis lacked precision (2.40, 95% CI: 0.73 – 7.86). No increased convulsion risk was observed following RV1 Dose 2. Overall, this study supports the favorable safety profile of RV1. Continued monitoring for safety signals through routine surveillance is needed to ensure vaccine safety.